Investigation on the Effects of Prefabricated Crack and Strain Rate on Uniaxial Compressive Properties of Frozen Silty Soil - Dongdong Ma; Ezra Esanju Kaunda; Kun Huang (Advances in Civil Engineering)
To investigate the uniaxial compressive strength and deformation properties of frozen silty soil with prefabricated crack under various strain rates, the static uniaxial compressive tests were conducted for frozen silty soil using three kinds of binder materials to select the suitable prefabricated crack manufacturing method. Afterward, the static and dynamic stress-strain curves of frozen silty soil with different prefabricated crack numbers were obtained based on static and splitting Hopkinson pressure bar (SHPB) tests. In addition, the high-speed camera was employed to record the fracturing process of frozen silty soil under impact loads. Results indicated that the frozen silty soil specimens with no binder showed higher static strength compared with other two binder materials (plaster and Vaseline). The strength growth rate of frozen silty soil showed three-stage (fast-slow-rapid) change characteristics. The peak strain of frozen silty soil under static loads scope was higher compared with that under dynamic loads, while its dynamic peak strain with various prefabricated crack numbers was remarkably rate-dependent. The absorbed energy density of frozen silty soil was subject to a negative (positive) relationship with the prefabricated crack numbers (strain rate). The dominated crack of intact frozen silty soil specimen finally presented Y-shaped shear failure. However, tensile cracks parallel to stress wave propagation direction were observed for the frozen silty soil specimen with prefabricated crack.